The problem of repatriation of Circassian immigrants from the Ottoman empire in the second half of the 19th – beginning of the 20th centuries in the documents of the archives of Russia and Georgia - Anzor V., Kushkhabiev (Kavkazologiya, 2023)
The documents analyzed in the article are classified into 2 types – office documentation and regula-tory legal acts. Documents of the 1st type are divided into 2 groups depending on the departments of their compilation and functions. The first set of papers includes official correspondence and re-ports from Russian ambassadors in the Ottoman Empire to the Russian Minister of Foreign Affairs, as well as correspondence from Russian consuls and vice-consuls in Ottoman Empire provinces to Russian diplomats in Constantinople. The papers explain how Circassians came to the Ottoman Empire and the difficulties they faced when attempting to return home. The second group consists of documents prepared by military officials in the Caucasus: instructions from the Viceroy of the Caucasus’s Main Directorate to lower-ranking commanders of subdivisions, heads of regions and territories, instructions from the Commander-in-chief of civil authority in the Caucasus to governors-general and heads of regions and districts of the Caucasus region, etc., military officials’ reports to higher levels, attitudes between departments o According to these records, military officials in the Caucasus sent instructions to their subordinates in early 1861, which included rules addressing North Caucasian repatriates. Similar documents were accepted by tsarist officials in the Caucasus and at the beginning of the 20th century. The regulatory legal acts include: the provision of the Committee of Ministers «on taking measures to suspend the return of the highlanders from Turkey... », developed in July 1861 and approved by the emperor; «Regulations regarding Caucasian settlers returning from Turkey» (09.1861), compiled by the Chief of the General Staff of the Caucasian Army A.P. Kartsov. They contain rules that should have been applied to different groups of North Caucasian repatriates.